Pengaruh Brand Ambassador NCT Dream Dan E-WOM (Electronic Word Of Mouth) Terhadap Keputusan Pembelian Snack Tos Tos Tortilla Chips - Delicia, Eliza; ., Roslina; Wulan, Mutiasari Nur (CV. ITTC INDONESIA, 2025)
Competition in the snack food industry in Indonesia is becoming increasingly intense, particularly among the younger generation such as Gen Z, who are the primary consumers. PT. Dua Kelinci, through its product TosTos Tortilla Chips, collaborates with the South Korean boy group NCT Dream as Brand Ambassador and utilizes an Electronic Word of Mouth (E-WOM) strategy to enhance purchase decisions. This study aims to examine the influence of NCT Dream as Brand Ambassador and Electronic Word of Mouth (E-WOM) on the purchase decision of TosTos Tortilla Chips. The research employs a quantitative approach with data collected through questionnaires distributed to 210 respondents, selected using a Nonprobability Sampling method with a Purposive Sampling technique. Data analysis was conducted using multiple linear regression and hypothesis testing through partial test (t-test). The results indicate that both Brand Ambassador and Electronic Word of Mouth (E-WOM) have a positive and significant influence on the purchase decision of TosTos Tortilla Chips.